PENGARUH CUSTOMER EXPERIENCE, DIGITAL MARKETING DAN FASILITAS WISATA TERHADAP MINAT KUNJUNGAN PADA OBYEK WISATA SUBAN AIR PANAS KABUPATEN REJANG LEBONG. - Alfarabi, Dio Zaki; Pribowo, Muhammad Galy Njoman Ari (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
The purpose of this research is to find out whether Customer Experience (X1), Digital Marketing (X2), and Tourist Facilities (X3) influence Visiting Interest (Y) at the Suban Hot Springs tourist attraction, Rejang Lebong Regency. The population in this study are students who at Muhammadiyah University of Bengkulu. totaling 180 respondents. The sampling technique used accidental sampling based on predetermined criteria, totaling 180 respondents. The processed data was analyzed using the SPSS 26 formula. Based on the results of research and analysis of the influence of the Customer Experience (X1), Digital Marketing (X2) and Tourist Facilities (X3) variables on interest in visiting the Suban Hot Springs tourist attraction, Rejang Lebong Regency. The following conclusion can be drawn: Customer Experience (X1) has a positive effect on consumer interest in visiting (Y) at the Suban Hot Springs tourist attraction, Rejang Lebong Regency. Digital Marketing (X2) has a positive effect on consumer interest in visiting (Y) at the Suban Hot Springs tourist attraction, Rejang Lebong Regency. Tourist Facilities (X3) have a positive effect regarding consumer interest in visiting (Y) at the Suban Hot Springs tourist attraction, Rejang Lebong Regency. Keywords: Customer Experience, and Digital Marketing of tourist facilities and interest in visiting.